1975
DOI: 10.1104/pp.55.2.390
|View full text |Cite
|
Sign up to set email alerts
|

Action of Nalidixic Acid on Chloroplast Replication in Euglena gracilis

Abstract: The role of light in nalidixic acid bleaching of Euglena gracilis var. bacillaris was investigated. The kinetics of loss of the chloroplast-associated DNA and the sensitivity of chloroplast replication to ultraviolet light was followed during treatment with nalidixic acid. By using the mutant P4ZUL, and 3-(3,4-dichlorophenyl)-, 1-dimethylurea, it was demonstrated that the requirement for light was a functioning photosynthetic electron transport system. Ultracentifugal analysis showed a substantial decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…DNA supercoiling which results from the double stranded DNA break-and-reunion activity of these enzymes is suggested to be important to the process of DNA replication, recombination and transcription (10). The fact that ctDNA replication in Euglena is inhibited by naladixic acid (29), an inhibitor which specifically interferes (13) with subunit A activity (nicking-closing) of topoisomerase, supports this hypothesis.…”
Section: Discussionsupporting
confidence: 56%
“…DNA supercoiling which results from the double stranded DNA break-and-reunion activity of these enzymes is suggested to be important to the process of DNA replication, recombination and transcription (10). The fact that ctDNA replication in Euglena is inhibited by naladixic acid (29), an inhibitor which specifically interferes (13) with subunit A activity (nicking-closing) of topoisomerase, supports this hypothesis.…”
Section: Discussionsupporting
confidence: 56%
“…Little information is available on the repair of single strand or double stranded breaks after ionizing radiation in plants (19). It seems that some spinach chloroplast division like that in tobacco (1) and Euglena (17) (12), and Possingham (20), an increase in cell size is probably a prerequisite for an increase in chloroplast numbers. The present radiation studies reiterate the relationship between the two processes.…”
Section: Methodsmentioning
confidence: 99%
“…It is now established that there are many DNA copies in chloroplasts (16). More recently, it has been shown that in Euglena plastids can replicate using a reduced number of genomes (17).…”
mentioning
confidence: 99%
“…Lyman (15) and Lyman et al (16) concluded from their results that chloroplast replication is inhibited as a result of the loss of the chloroplast DNA induced by NAL . Their studies, however, do not prove that the chloroplasts did not replicate and subsequently were diluted out after the loss of chloroplast DNA.…”
mentioning
confidence: 99%
“…Nalidixic acid (NAL), a potent inhibitor of DNA replication that affects DNA gyrase in prokaryotes (6,7,23), is one agent that causes the bleaching of Euglena gracilis (15,16,19,20). Pienkos et al (20) and Lyman et al (16) used CsC1 equilibration analysis to show that NAL induced loss of chloroplast DNA, which resulted in the inability to form green colonies.…”
mentioning
confidence: 99%